2019
DOI: 10.1021/acs.jmedchem.9b00123
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics-Driven Optimization of 4(3H)-Pyrimidinones as Phosphodiesterase Type 5 Inhibitors Leading to TPN171, a Clinical Candidate for the Treatment of Pulmonary Arterial Hypertension

Abstract: Phosphodiesterase type 5 (PDE5) inhibitors are first-line therapy for pulmonary arterial hypertension (PAH) and erectile dysfunction. As a continuing work to improve the terminal half-lives and oral bioavailabilities of our previously reported 4(3H)-pyrimidones, a pharmacokineticsdriven optimization focusing on the terminal substituent is described. Two major congeneric series of 4(3H)-pyrimidones, the aminosulfonylphenylpyrimidones and acylaminophenylpyrimidones, were designed, synthesized, and pharmacologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 39 publications
2
34
0
Order By: Relevance
“…In 2017, Chekol et al [72] reported on two novel PDE5-specific radioligands, [ 11 C]15 and [ 18 F]16 (see Figure 4), for evaluation of the enzyme expression and occupancy in lung, heart and brain by PET. [76,77]as well as the PDE5 inhibitors tadalafil [78,79], vardenafil [78,80] and sildenafil [78][79][80].…”
Section: Pde5 Radioligandsmentioning
confidence: 99%
See 3 more Smart Citations
“…In 2017, Chekol et al [72] reported on two novel PDE5-specific radioligands, [ 11 C]15 and [ 18 F]16 (see Figure 4), for evaluation of the enzyme expression and occupancy in lung, heart and brain by PET. [76,77]as well as the PDE5 inhibitors tadalafil [78,79], vardenafil [78,80] and sildenafil [78][79][80].…”
Section: Pde5 Radioligandsmentioning
confidence: 99%
“…Out of a series of pyridopyrazinone derivatives, compounds 15 and 16 showed highest inhibitory potency towards PDE5 (Figure 4) and were subsequently selected for radiolabeling. Starting from the corresponding desmethyl or tosylate precursors, [ 11 [76,77]as well as the PDE5 inhibitors tadalafil [78,79], vardenafil [78,80] and sildenafil [78][79][80].…”
Section: Pde5 Radioligandsmentioning
confidence: 99%
See 2 more Smart Citations
“…12 In preclinical experiments, TPN171H was proved to have good selectivity, exhibit satisfactory safety and pharmacokinetic profiles in rats and dogs, and exert a longer-lasting effect than sildenafil in animal models. 13 Therefore, we conducted this study to evaluate the safety, tolerability, and pharmacokinetics of TPN171H in healthy subjects after single and multiple dosing, in addition, to investigate the food effect on pharmacokinetics and safety of TPN171H.…”
Section: Introductionmentioning
confidence: 99%